Design concept of novel balanced multi-band antenna for sensor - LV Wen-jun1; ZHU Hong-bo1 (Tongxin xuebao)
Design concept of a novel balanced multi-band tag antenna for Internet of things sensors applications was proposed.The antenna has a symmetrical structure so that it can be easily and directly integrated with differential driving RF front ends.The antenna’s surface current distribution,radiation patterns,impedance matching characteristics and gain,were numerically studied by using computer simulations,and the operating principle of the antenna was determined.Based on the numerically and basic experimental results,it is concluded that the antenna has a compact size and moderate gain,and can cover the bands of 2.4～2.5GHz/5.1～12GHz,which are for RFID and short-range wireless access applications.Thus the antenna can be used as tag antenna for wireless sensors in Internet of things.